SISTEM PENGATUR SUHU KELEMBABAN RUANGAN PADA BUDIDAYA JAMUR TIRAM BERBASIS ARDUINO - Mansur Ponimat; Sujjada, Alun (LPPM UNIKA Santo Thomas, 2021)
One of the businesses that is often in demand by farmers is cultivating oyster mushrooms because oyster mushrooms are very tasty and have many health benefits, but cultivating oyster mushrooms requires quite complicated care, if the temperature and humidity of the environment where the mushrooms grow are abnormal, it will inhibit the growth of the fungus. With this research the author aims to create a system that can regulate and monitor temperature in real time so that fungal growth will be more fertile and increase production. The development method used to make this research is the waterfall method, this method is very easy to use and is able to solve problems quickly. The main purpose of this research is to create a system that can assist oyster mushroom farmers in regulating and monitoring temperature conditions by using a fan and a water pump as a medium for cooling the temperature which is regulated by an Arduino microcontroller.